2007
DOI: 10.1016/j.joca.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Elevated high-sensitivity C-reactive protein levels are associated with local inflammatory findings in patients with osteoarthritis

Abstract: These results suggest that systemic hsCRP levels reflect synovial inflammation in OA patients, perhaps by means of synovial IL-6 production. Future studies are needed to clarify how these infiltrates and their products may contribute to disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
214
5
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(242 citation statements)
references
References 40 publications
17
214
5
6
Order By: Relevance
“…However, after vitamin E supplementation, no significant reduction in plasma CRP and synovial fluid IL-6 were observed. Our findings were inconsistent with the findings of Pearle and colleagues who observed that elevated CRP levels in OA were associated with local inflammation [Pearle et al 2007]. Although CRP is a nonspecific marker, we observed a positive correlation between CRP and other factors such as BMI, which explained its association with knee OA up to certain extent.…”
Section: Discussioncontrasting
confidence: 99%
“…However, after vitamin E supplementation, no significant reduction in plasma CRP and synovial fluid IL-6 were observed. Our findings were inconsistent with the findings of Pearle and colleagues who observed that elevated CRP levels in OA were associated with local inflammation [Pearle et al 2007]. Although CRP is a nonspecific marker, we observed a positive correlation between CRP and other factors such as BMI, which explained its association with knee OA up to certain extent.…”
Section: Discussioncontrasting
confidence: 99%
“…Those with positive CRP results had greater chance to acquire knee OA in contrast to negative CRP findings which had a protective effect. This is in accordance with the three studies done in USA [20][21][22] where they found a correlation between patients with elevated CRP and the presence of inflammatory changes in patients with KOA. They illustrated that the elevated CRP levels seen in these patients might reflect local inflammation within the joint and Interleukin 6(IL-6) is known to be the chief regulator of CRP production and may have a role in the inflammatory OA process.…”
Section: Methodssupporting
confidence: 92%
“…Most of CRP positive knee OA patients were overweight in contrast to CRP negative patients, were the majority of them had normal BMI so overweight were associated with the highest risk of developing Knee OA with positive C-reactive protein, this finding was in consistence with Engström et al 28 and Virginia et al 27 In USA a study done in 2007 contrasted our finding's as they observed no association between systemic CRP (r = 0.09, P = 0.56) and BMI (r = 0.004 ,P = 0.97) in KOA patients. 22 Another interesting finding in our study was a significant association between CRP and family history. Most of CRP positive knee OA patients had positive family history, this agreed with Vonk et al 29 reported that Micro RNAs (mi RNAs) most likely modulate cartilage metabolism through metabolic and inflammatory mechanisms in OA.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations